THE PORTRAYAL OF GISELLE’S CHARACTER IN “ENCHANTED” MOVIE: A GENDER STEREOTYPE STUDY - Rizqia Lutfi Kurnia Dewi; Ahmad Muhid; Didit Kurniadi (Universitas Aki, 2022)
Enchanted (2007) is a musical romantic comedy movie produced by Walt Disney Pictures that combine animated and live action scenes. The movie has interesting characters and plot to analyze. This study examines Giselle’s character in Disney’s Enchanted movie, the connection with gender-role stereotypes, and the moral values from the story. Data were collected by using library research method and analyzed through structural approach and coded content analysis approach based on coding characteristics. Results showed that Giselle has more feminine than masculine characteristics that confirm the female gender-role stereotype. However, a twist at the climax of the story displaying her acquired masculine traits indicates the rise of modern female-gendered representation from Disney. Further studies are needed to investigate the development of the dynamic character related to Disney’s gender-role message and the influences to today society life.